Diagnósticos de enfermagem em pacientes internados por acidente vascular encefálico - Cavalcante, Tahissa Frota (2008)
The idetinfication of the diagnoses in nursing contribute to the planning of the nursing interventions in order to prevent and reduce the incapabilities. It was aimed to analize the nursing diagnosis profile in patients with stroke during hospitalization. This is a descriptive study which was done within the period of October 2007 to April 2008, involving 91 patients with stroke, who were hospitalized in an emergency department of a general hospital set in Fortaleza City - Ceará. Some including criteria were established: a) being hospitalized due to the stroke diagnosed by the doctor, independently on the type; b) being 18 years old or over; c) not having previous history of stroke. The excluding criteria were: a) patients who, during the collection of data, presented emergencial situations as well as dead risk. A form was used for the data collection and it also undergone content validation with four nurses who are expertise in nursing diagnoses or in the care of patients with stroke. The information was collected through enterview, physical test and prontuary consultation. To name the nursing diagnoses, the Taxonomy II proposed by the North American Nursing Diagnosis Association published in 2008 was followed as reference. The data was compiled in the Excel program and the statistic analysis was done within the SPSS program. The level of significance adopted in the study was of 5%. Taking the social and demographic data into account, it was verified that the majority of these patients were from feminine gender, retired, catholics, lived with a partner and had low education and income. The ischemic type of stroke was predominant in the group (45.9%), followed by the hemorrhagic type (38.5%). According to the findings, these patients showed an avarage of nine nursing diagnoses, eleven defining characteristics, six related factors and five risky factors. The most frequent nursing diagnoses were: Risk of infection (96.7%), Self-care deficit_bathing and higiene (76.9%), Self-care deficit_intimate higiene (74.7%), Self-care deficit_self dressing (71.4%), Verbally damaged communication (62.6%), Ineffective tissular perfusion_cerebral type (59.3%), Risk of the integrity of the damaged skin (52.7%) and Risk of aspiration (50.5%). Generally, the profile found in this study is similar to the ones described in other studies with patients hospitalized in intensive therapy units. Apart from the nursing diagnosis Risk of infection, the remaining ones showed statistically significant association among themselves. The total defining characteristics and the related factors revealed significative statistic association with all nursing diagnoses, except from the Risk of infection one. As observed, the study allowed us to know in a deep way the nursing diagnoses, the defining characteristics, the related factors and the risk factors manifested in the patients during hospitalization. The presence of those with biological and risky character stands out. The findings reinforce the need that the nursing team has to act not only upon the curative aspect, but also on the prevention and the health promotion, in the secondary levels of health and the tertiary as well